1999
DOI: 10.1136/oem.56.10.691
|View full text |Cite
|
Sign up to set email alerts
|

Preventing commercial fishing deaths in Alaska.

Abstract: Objectives-To evaluate the eVectiveness of the United States Commercial Fishing Industry Vessel Safety Act of 1988 in reducing the high occupational death rate (200/100 000/year in 1991-2) among Alaska's commercial fishermen. Methods-Comprehensive surveillance of deaths in commercial fishing was established by our oYce during 1991 and 1992 for Alaska. Demographic data and data on risk factors and incidents were compiled and analysed for trend. Results-During 1991-8, there was a significant (p<0.001) decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 5 publications
(1 reference statement)
0
42
0
Order By: Relevance
“…It also found that the two leading causes of vessel disaster in the GoM were flooding and collision, as shown in Figure 2 [18].…”
Section: Gulf Of Mexico (Gom)-related Fatality Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…It also found that the two leading causes of vessel disaster in the GoM were flooding and collision, as shown in Figure 2 [18].…”
Section: Gulf Of Mexico (Gom)-related Fatality Studiesmentioning
confidence: 94%
“…In 2010, CDC reported on 504 US commercial fishing fatalities for the years 2000-2009 [18]. The sources of the data included reports from the USCG, enforcement agencies, media, death certificates, and state-based systems.…”
Section: Gulf Of Mexico (Gom)-related Fatality Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature in other maritime industries suggests cold stress should be a serious concern, but unique factors limit the generalizability of these findings [26]. Although cold temperatures contribute to cold stress, factors such as clothing insulation, thermogenesis from movement, personal experience, cold perception and subjective discomfort have all been shown to moderate the thermal stress/performance relationship [27].…”
Section: Introductionmentioning
confidence: 99%
“…Other states with substantial shorelines (rivers, lakes and marine), colder climates and sizeable rural populations (Michigan, Minnesota, Ohio and Maine) had drowning death rates between 1.25 and 1.81 per 100,000. Although several drowning prevention programs have been instituted and significant research has focused on occupational drowning deaths in Alaska, there has been limited examination of non-occupational drowning data (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%